Sustained censorship in JO (2026-04) (Jordan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Jordan. Data sourced from OONI.
Censorship Incident ID: JO-2026-0203. Severity: critical. Confidence: 80%